Thermodynamic Analysis of the Self‐Assembly of Pseudo Isocyanine Chloride in the Presence of Crowding Agents. Issue 3 (3rd February 2021) - Hämisch, Benjamin; Pollak, Roland; Ebbinghaus, Simon; Huber, Klaus
Abstract: Pseudo isocyanine chloride (PIC) is a water‐soluble cationic dyestuff, which self‐assembles to fiber‐like aggregates below a characteristic temperature threshold. The threshold temperature decreases with decreasing PIC concentration. Macromolecular cosolutes affect this self‐assembly of PIC, similar to the impact macromolecular crowding has on the aggregation of proteins in living systems. The present study analyses the impact of triethylene glycol (TEG), polyethylene glycol (PEG), and Ficoll 400 as synthetic macromolecular crowding agents on the self‐assembly of PIC. A drastic change in the absorption behavior of visible light by PIC, which accompanies the transformation of monomeric PIC to the aggregate state of PIC, allows to analyze the temperature‐dependent self‐assembly in detail. Assisted by calorimetric measurements and by an analogy between self‐assembly and chemical polymerization, the thermodynamic analysis allowed to interpret the observed tendency of TEG and PEG to suppress and of Ficoll 400 to promote self‐assembly of PIC. Whereas the suppression by TEG and PEG can be attributed to preferential interactions between TEG or PEG and PIC, the promoting effect induced by Ficoll 400 is caused by excluded volume effects exerted by Ficoll. The results are in support of PIC as a cheap substitute of proteins in test tube studies of self‐assembly and as sensor for crowding effects on self‐assembly processes in cells. Abstract : Like peas in a pod : The aggregation of the dyestuff pseudo isocyanine chloride (PIC) exhibits various similarities towards the self‐assembly of proteins. Addition of synthetic crowding agents to mimic a cellular environment modulates the aggregation of PIC. A thermodynamic analysis revealed that volume exclusion introduced by Ficoll promoted aggregation whereas attractive interactions to PEG or TEG as additives hampered aggregation.